Before Command:An Economic History of Russia from Emancipation to the First Five-Year - Paul R. Gregory (Princeton University Press, 2014)
THIS BOOK summarizes the research that I have done on the Russian and early Soviet economies over the past twenty-five years. As a graduate student working with Simon Kuznets, Abram Bergson, and Henry Rosovsky, I wrote my first paper on the level of Russian economic development—a paper that became my first publication. After this first effort, having discovered that I enjoyed doing empirical work, I set about for the next quarter of a century investigating the quantitative foundations of the late Russian and early Soviet economies. The statistical raw material for each period was rich and largely unexplored. Moreover, much of the historical work done on these early periods resulted in grand theories or conclusions that were poorly or not at all grounded in the underlying data. Lenin wished to show that the Russian economy was the "weak link" in the capitalist chain. Alexander Gerschenkron used the Russian economy to develop his relative backwardness theory. Historians, without a serious investigation of the available data, became convinced that an agrarian crisis had occurred after emancipation. I was fortunate to have the support of the National Science Foundation in the mid-1970s for my work on the tsarist period and again in the late 1980s and early 1990s for my work on the 1920s. The generous support of the Humboldt Foundation allowed me to do research in the best libraries of Europe in the late 1970s. I wrote one monograph and quite a few articles during this period. Some found their way into economics journals, others into Russian studies journals, and yet others into collections and festschriften. Taken in their entirety, these publications present a picture of the Russian and early Soviet economies that is different from many of the standard versions of this period. It was for this reason that I concluded it would be useful to write a second monograph summarizing my findings and pointing out the ways in which they dispute previous findings.